2016
DOI: 10.1021/acs.est.6b02077
|View full text |Cite
|
Sign up to set email alerts
|

Electron Shuttles Enhance Anaerobic Ammonium Oxidation Coupled to Iron(III) Reduction

Abstract: Anaerobic ammonium oxidation coupled to iron­(III) reduction, termed Feammox, is a newly discovered nitrogen cycling process. However, little is known about the roles of electron shuttles in the Feammox reactions. In this study, two forms of Fe­(III) (oxyhydr)­oxide ferrihydrite (ex situ ferrihydrite and in situ ferrihydrite) were used in dissimilatory Fe­(III) reduction (DIR) enrichments from paddy soil. Evidence for Feammox in DIR enrichments was demonstrated using the 15N-isotope tracing technique. The exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 245 publications
(102 citation statements)
references
References 53 publications
6
96
0
Order By: Relevance
“…(A,B) ferrous iron production, (C,D) acetate turnover, (E,F) CO 2 production, and (G,H) CH 4 production. Data (A–D) of these three setups (CK abiotic, CK biotic, and powdered biochar biotic) in both the enrichments has been described before (Zhou et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(A,B) ferrous iron production, (C,D) acetate turnover, (E,F) CO 2 production, and (G,H) CH 4 production. Data (A–D) of these three setups (CK abiotic, CK biotic, and powdered biochar biotic) in both the enrichments has been described before (Zhou et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…This might result from the higher concentration of salts contained in the in situ ferrihydrite enrichment when preparing the in situ ferrihydrite (Zhou et al, 2016). In addition, other elements (e.g., P, Ni, Al, Se, et al, from the medium) might be incorporated into in situ ferrihydrite during its formation (Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that AQDS can function as an electron shuttle to facilitate feammox, which indicates that bacterial AQDS reduction is also coupled to ammonia oxidation (Zhou et al 2016). Therefore, humic substances, which are rich in quinone moieties like AQDS, are likely to be potential electron acceptors of bacterial ammonia oxidation despite no evidence yet.…”
Section: Feammoxmentioning
confidence: 99%